AMPK activation modulates IL‐36‐induced inflammatory responses by regulating IκBζ expression in the skin - Huang, Yi‐Ting; Chiu, Ling‐Ya; Lu, Po‐Hsuan; Hsiao, Pa‐Fan; Wang, Jen‐Yu; Lu, Ping‐Hsun; Wu, Nan‐Lin (British journal of pharmacology, 2024)
Background and Purpose The interleukin (IL)‐36 pathway is a critical player in the pathogenesis of pustular psoriasis. However, therapies targeting this pathway are limited or unaffordable (e.g. the anti‐IL‐36 receptor antibody). AMP‐activated protein kinase (AMPK), a regulator of cellular energy and metabolism, is known to participate in inflammatory diseases. However, its role in IL‐36‐induced skin inflammation remains unclear. Therefore, we sought to investigate the role of AMPK signals in regulating IL‐36‐induced responses in the skin. Experimental Approach IL‐36‐stimulated primary normal human epidermal keratinocytes (NHEKs) and IL‐36‐injected (intradermally) BALB/c mice served as the cell and animal models, respectively. Additionally, 5‐aminoimidazole‐4‐carboxamide riboside (AICAR) and A769662 served as AMPK activators. Key Results AICAR and A769662 significantly suppressed the IL‐36‐induced IL‐8 (CXCL8) and CCL20 production from NHEKs. IL‐36‐induced IκBζ protein expression was prominently reduced and IKK/IκBα phosphorylation was attenuated by AICAR and A769662. Conversely, AMPKα knockdown increased IκBζ protein expression and IKK/IκBα phosphorylation in IL‐36‐treated NHEKs. Furthermore, AICAR and A769662 enhanced IL‐36‐induced‐IκBζ protein degradation via the proteasome‐dependent but not the lysosome‐dependent pathway. Pretreatment of NHEKs with IL‐36 slightly suppressed the AICAR‐ and A769662‐triggered phosphorylation of AMPK and acetyl‐CoA carboxylase. In the mouse model, topical application of AICAR significantly reduced ear swelling, redness, epidermal thickening, neutrophil infiltration and inflammatory and antimicrobial peptide gene expression. Conclusion and Implications AMPK activation suppresses IL‐36‐induced IL‐8 and CCL20 release by regulating IκBζ expression in keratinocytes and reduces IL‐36‐induced skin inflammation in mice, suggesting that AMPK activation is a potential strategy for treating patients with IL‐36‐mediated inflammatory skin disorders.